2018
DOI: 10.1007/s11239-018-1711-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of catheter related thrombosis (CRT) in patients with acute leukemia using a platelet-adjusted low molecular weight heparin regimen

Abstract: Patients with acute leukemia frequently develop catheter-related thrombosis (CRT) despite concurrent thrombocytopenia. The incidence, treatment and outcomes of this complication are poorly documented. We undertook this study to determine the incidence of CRT in patients with acute leukemia and assess the safety and effectiveness of a treatment strategy using a platelet-adjusted low molecular weight heparin (LMWH) dosing protocol. Patients (18 years and older) with newly diagnosed acute leukemia from January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Thirty-five studies were evaluated as full text, and 20 of these with a total of 1473 patients were included in the analysis (Table 1). 15,21,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Study size ranged from 10 to 210 patients. Eleven studies were prospective and nine had a retrospective design.…”
Section: Re Sultsmentioning
confidence: 99%
“…Thirty-five studies were evaluated as full text, and 20 of these with a total of 1473 patients were included in the analysis (Table 1). 15,21,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Study size ranged from 10 to 210 patients. Eleven studies were prospective and nine had a retrospective design.…”
Section: Re Sultsmentioning
confidence: 99%
“…42 We found that 11% of pediatric cancer patients with a catheter inserted suffered from CVC-related VTE, which is considered equal to that of adults. 9,10 The incidence of CVC-related VTE in adults with ALL has been reported to range from 6.5 to 11.7%, 43,44 and from 3.8 to 13% in adults with solid tumors and a catheter. 45,46 Five studies described specifically CVC-related VTE in 459 children with ALL and 69 CVC-related VTE (15%).…”
Section: Discussionmentioning
confidence: 99%
“…In such patients, platelet count-adjusted LMWH dosing (in acute VTE) or temporarily withholding anticoagulation (in chronic VTE) are reasonable options. 10,11 A retrospective management study supports an individualized, risk-adapted approach to cancer patients with acute VTE and thrombocytopenia. While subtherapeutic LMWH dosages were generally preferred in patients with platelet counts of less than 100 Â 10 9 /L or the presence of cerebral metastasis, patients with PE or symptomatic VTE were more likely to receive therapeutic-dose anticoagulation.…”
Section: Management Of Venous Thromboembolismmentioning
confidence: 94%